ANALISA PENERAPAN PERATURAN PEMERINTAH NOMOR 60 TAHUN 2008 TENTANG SISTEM PENGENDALIAN INTERN PEMERINTAH OLEH INSPEKTORAT DI PROVINSI SULAWESI UTARA - Korah, Theyza; Karamoy, Herman; Kalangi, Lintje (ACCOUNTABILITY, 2016)
This research done to Analyze The Implementation Of Government Regulation Number 60 Of 2008 Concerning Internal Control Systems Of Government views from the north sulawesi 5 control elements. This is descriptive qualitative research, with developing framework to analyze think. Process and meaning. Research subjects required by using purposive sampling technique.Iepemelihan informants based researchers from consideration of certain criteria, that may be as much information from various sources. The study performed in three object of research, research and this indicates that the Government In The Province Of North Sulawesi already implement effective regulation of internal control systems and needs a good cooperation in applying such regulations as between the inspectorate of internal control and inspection unit working as object. Keywords ; Government Regulation Number 60 Of 2008, 5 Elements Of Internal Control